Buddhist Approaches to Cultural Ecology: A Case Study of Shanghai Jade Buddha Temple - Ting, Ven. Ti (Journal of International Buddhist Studies, 2023)
Relatively speaking, cultural ecology in the Buddhist circle is a new area of study. This article, taking Shanghai Jade Buddha Temple (JBT) as a case, delineates the cultural changes in JBT through three areas: 1) JBT adapts to the socialist society; 2) JBT devotes to community services, and 3) JBT cares about the living planet. Through the analysis of these areas, it is found that Buddhists’ practices and works in JBT have been greatly changed under the background of modern society, and temple in metropolis. In the view of cultural ecology study, this “change” or “adaptation” as some researchers called, demonstrates the cultural process that Buddhism is being reproduced within the given environment of Shanghai regional culture.